Acute effects of isoinertial resistance application on sprint, vertical and horizontal jump performance - M. Kale; A. Özmusul; E. Heper (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Purpose: The purpose of this study was to investigate of the acute effects of isoinertial resistance application on sprint, vertical and horizontal jump performance. Material: Volunteered 32 male students were divided into randomized experimental group and control group. Before and after 4-repetition maximal back squat with (for experimental group) or without isoinertial resistance application (for control group), 30 m sprint, vertical squat and countermovement jump tests with both legs, dominant leg, and non-dominant leg, standing broad jump and standing broad countermovement jump tests with both legs were assessed. Wilcoxon t test for pre- and post-test differences within the group, and Mann Whitney U test for pre- and post-test differences between the groups were used. Results: There were no significant differences within the group and between the groups for 30m both legs sprint parameters except pre-test mean stride length between the groups (Z=-2.27; p<0.02). Control group had a significant difference between pre- and post-test dominant leg vertical force (Z=-2.07; p<0.05). There were significant group differences in pre-test non-dominant leg countermovement jump (Z=-2.13; p<0.05), pre- and post-test non-dominant leg stride length (Z=-1.99 and Z=-2.28; p˂0.05, respectively). Conclusions: As a result of the effect of acute isoinertial resistance application to stride length especially to non-dominant stride length it is concluded that long-term isoinertial resistance training can support sprint performance with tolerating stride length imbalance between dominant leg and non-dominant leg.